Extension of the Random-Effects Regression Algorithm to Account for the Effects of Nonlinear Site Response - Stafford,PJ (Bulletin of the Seismological Society of America, 2015)
The random-effects regression algorithm, made popular within engineeringseismology by Abrahamson and Youngs (1992), is arguably the most commonly usedapproach for developing empirical ground-motion models. The original presentation ofthis algorithm relates to the most simple application of a far more general mixed-effectsmodel formulation. In recent years, it has become increasingly common to incorporatenonlinear site response effects within empirical, or semi-empirical, ground-motion models,but the original random-effects algorithm does not apply to cases in which the randomeffects enter the model in a nonlinear manner. This article presents a more generalalgorithm for fitting mixed-effects models that can accommodate nonlinear site effects(among other effects). The presented algorithm deliberately mirrors that of Abrahamsonand Youngs (1992) but allows for the treatment of far more elaborate variance structures.